2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high frequency rTMS on sleep deprivation: A pilot study

Abstract: Transcranial magnetic stimulation is a neurostimulation technique which has the potential to serve as a unique research tool for investigating a wide variety of fields in cognitive neuroscience. TMS has been approved by the FDA to serve as a treatment to depression and has also been used to evaluate its effects among several conditions such as Alzheimer, Parkinson disease, chronic pain and stroke. High frequency TMS has been previously used with the intention to measure and modulate the negative effects of sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Few years later, the same research group showed the beneficial effects of rTMS after 4 sessions of concurrent rTMS/task performance given over the course of 2 days of SD ( Luber et al, 2013 ). Similar results were reported by other authors, with 5 Hz-rTMS over the left middle occipital gyrus, resulting in greater accuracy and shorter response times after SD ( Martinez-Cancino et al, 2016 ; Guo et al, 2019 ). Lastly, a recent study has evaluated the effect of high-frequency rTMS on reversing the negative effects of SD for 24 h in 66 healthy individuals randomized into “real” rTMS group and “sham” group ( Li et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Few years later, the same research group showed the beneficial effects of rTMS after 4 sessions of concurrent rTMS/task performance given over the course of 2 days of SD ( Luber et al, 2013 ). Similar results were reported by other authors, with 5 Hz-rTMS over the left middle occipital gyrus, resulting in greater accuracy and shorter response times after SD ( Martinez-Cancino et al, 2016 ; Guo et al, 2019 ). Lastly, a recent study has evaluated the effect of high-frequency rTMS on reversing the negative effects of SD for 24 h in 66 healthy individuals randomized into “real” rTMS group and “sham” group ( Li et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Previous rTMS studies on patients with cognition impairment in Alzheimer's disease, Parkinson's disease, schizophrenia, and dementia in older patients have reported significant positive effectiveness on improving cognitive ability [23][24][25][26]. Similar results were reported in both animal and human studies on SD which also observed the potential effectiveness of rTMS for the treatment of cognitive impairment induced by SD, especially the working memory [27][28][29][30][31]. One human study also observed the significant correlation between the cortical activation changes induced by SD and the enhanced working memory performance during rTMS over the identical cortical site.…”
Section: Introductionsupporting
confidence: 77%
“…Neural Plasticity parasagittal plane [33]. Numerous studies on the effect of SD on working memory, which used the N-back task, have found decreased activation mainly in the frontal lobe [27]. Studies with PET also have observed lower metabolism in prefrontal and parietal areas due to lack of sleep [34].…”
Section: Rtms Proceduresmentioning
confidence: 99%
“…These Surprisingly, subjects' performance on the digit span task was better the morning after alcohol compared to placebo. This is inconsistent with reports that both acute alcohol and sleep deprivation impair working memory function (Alhola & Polo-Kantola, 2007;Frenda & Fenn, 2016;Martinez-Cancino et al, 2016;Mintzer, 2007;Scott Saults et al, 2007;Stevens et al, 2022). Yet, other studies either did not detect the effects of intoxication on next-day cognitive and behavioral performance (Rohsenow et al, 2006(Rohsenow et al, , 2010 or found nonsignificant improvements in performance (Howland et al, 2010b).…”
Section: Discussionmentioning
confidence: 80%